Alimentação e estado nutricional de crianças nascidas pré-termo submetidas a um programa de estimulação sensóriomotora-oral - Capeleto, Duanne de Menezes (2010)
The sensory-motor-oral (SMO) stimulation during Intensive Care Neonatal period has been proposed in order to facilitate the transition from gavage to oral feeding and thereby promote weight gain, breastfeeding and minimize the difficulties in the introduction of solid foods during childhood. Objective: To determine whether the SMO stimulation influence the infant growth and the introduction of complementary feeding in children under two years old born preterm. Methods: Cross-sectional study that included 16 children, born preterm, randomly subjected to a program of sensory-motor-oral stimulation during their neonatal period. The children were assessed by anthropometric measurements and nutritional status was evaluated using the indicators P/E, P/I and E/I, according to the National Center Health Statistics (NCHS). Results: There was no statistical difference between groups regarding the z-score values for P/E, P/I, and E/I. In both groups children were classified as well-nourished. The duration of breastfeeding was higher among children stimulated when compared with the control with an average of 67.5 days and 30 days, respectively. The main reasons for early weaning from breastfeeding were the refusal of the children and insufficient milk production. The introduction of complementary foods occurred in the early period for both groups with an average of 5.8 months for the GE and 5.4 months for the GC. Three children (37.5%) in the CG and two (25%) in GE had difficulties when started with solid foods but there was no statistically significant difference. Conclusion: Based on these results, we could not confirm the benefit of a SMO stimulation program on nutritional status and body composition of children born preterm at age 12 to 24 months. However, the SMO stimulation seems to have a beneficial influence on the duration of exclusive breastfeeding and the introduction of solid foods.